Juridical Analysis of Hospital Obligations in Providing Emergency Medical Services - Z.Noor; A.Oktavianus (The Medical Journal of Hospital Management and Health Law, 2025)
Introduction: Emergency medical services constitute a fundamental component of the right to health, requiring immediate and non-discriminatory intervention to prevent mortality or permanent disability. This study analyzes the legal framework governing hospital obligations in emergency scenarios, particularly focusing on the tension between public law duties and private institutional autonomy. Methods: This research employs a normative juridical method, utilizing a statutory approach, conceptual analysis, and case study evaluations to examine relevant health legislation, ministerial regulations, and judicial precedents. Results: The findings indicate that statutory frameworks impose strict statutory duties on all healthcare facilities, irrespective of their public or private ownership, to provide immediate stabilization therapies without demanding upfront financial deposits. However, regulatory ambiguities regarding the definition of emergency thresholds and the mechanisms for state-backed financial reimbursement create systemic compliance vulnerabilities. Discussion: The literature review demonstrates that while international human rights standards recognize medical emergencies as non-derogable obligations, domestic enforcement often suffers from a lack of harmonization between administrative sanctions and civil liability. The legal gap centers on the protection of emergency physicians who face conflicting pressures between corporate hospital protocols and statutory healthcare mandates, necessitating clear legal protections and standardized triaging protocols. Conclusions: This study concludes that statutory hospital obligations must be reinforced by synchronized enforcement mechanisms and statefunded safety nets to ensure institutional compliance. It is recommended that regulatory bodies establish an objective legal definition of medical emergencies and formulate robust financial reimbursement policies to safeguard both patient rights and hospital sustainability.